Effect of rescue medication on seizure duration in non-institutionalized children with epilepsy. (January 2018) - Vigevano, Federico; Kirkham, Fenella J.; Wilken, Bernd; Raspall-Chaure, Miquel; Grebla, Regina; Lee, Dawn; Werner-Kiechle, Tamara; Lagae, Lieven
Abstract: Objectives: Characterize the real-world management of and outcomes for children with epilepsy receiving rescue medication for prolonged acute convulsive seizures (PACS) in the community. Methods: PERFECT-3 (Practices in Emergency and Rescue medication For Epilepsy managed with Community-administered Therapy 3) was a European, retrospective observational study. Eligible patients were non-institutionalized children with epilepsy aged 3–16 years who had experienced ≥1 PACS in the past year and had ≥1 currently prescribed PACS rescue medication. Investigators provided clinical assessments and parents/guardians completed questionnaires. Statistical tests were post hoc ; p values are descriptive. Results: At enrollment ( N = 286), most patients had prescriptions for diazepam (69.2%) and/or midazolam (55.9%); some had two (26.6%) or three (2.4%) prescribed rescue medications. Most patients experienced PACS despite regular anti-epilepsy medication. According to parents, the average duration of their child's seizures without rescue medication was <5 min in 35.7% of patients, 5–<20 min in 42.6%, and ≥20 min in 21.7% ( n = 258); with rescue medication seizure duration was <5 min in 69.4% of patients, 5–<20 min in 25.6%, and ≥20 min in 5.0%. Rescue medication use was significantly associated with average seizures lasting <5 min (χ 2 = 58.8; p < 0.0001). At the time of their most recent PACS, 58.5–67.8% of children reportedly received rescue medication within 5 min of seizure onset, and 85.4–94.1% within 10 min. Conclusion: This study provides the first real-world data that rescue medications administered in the community reduce the duration of PACS in children with epilepsy. Study limitations including potential recall bias are acknowledged. Highlights: Prolonged seizures in children with epilepsy may progress to status epilepticus. Benzodiazepine rescue medications can be effective in terminating seizures. This was an observational, retrospective study providing real-world data. Rescue medication was administered by parents, teachers or other caregivers. We report reduced seizure duration after administration of rescue medication.